Silicon nitride bio ceramics sintered by microwave exhibit excellent mechanical properties, cytocompatibility in vitro, and anti-bacterial properties - Jiayu He; Yuandong Liu; Xiaofeng Zeng; Yan Tong; Run Liu; Kan Wang; Xiangdong Shangguan; Guanzhou Qiu; Coswald Stephen Sipaut @ Mohd Nasri (MDPI, 2023)
Silicon nitride is a bioceramic with great potential, and multiple studies have demonstrated its biocompatibility and antibacterial properties. In this study, silicon nitride was prepared by a microwave sintering technique that was different from common production methods. SEM and pore distribution analysis revealed the microstructure of microwave-sintered silicon nitride with obvious pores. Mechanical performance analysis shows that microwave sintering can improve the mechanical properties of silicon nitride. The CCK-8 method was used to demonstrate that microwave-sintered silicon nitride has no cytotoxicity and good cytocompatibility. From SEM and CLSM observations, it was observed that there was good adhesion and cross-linking of cells during microwave-sintered silicon nitride, and the morphology of the cytoskeleton was good. Microwave-sintered silicon nitride has been proven to be non-cytotoxic. In addition, the antibacterial ability of microwave sintered silicon nitride against Staphylococcus aureus and Escherichia coli was tested, proving that it has a good antibacterial ability similar to the silicon nitride prepared by commonly used processes. Compared with silicon nitride prepared by gas pressure sintering technology, microwave-sintered silicon nitride has excellent performance in mechanical properties, cell compatibility, and antibacterial properties. This indicates its enormous potential as a substitute material for manufacturing bone implants.